Physical properties of molecular clouds at 2 pc resolution in the low-metallicity dwarf galaxy NGC 6822 and the Milky Way - Schruba, Andreas; Kruijssen, Diederik; Bigiel, Frank (The astrophysical journal. Part 2, Letters, 2017)
We present the Atacama Large Millimeter/submillimeter Array survey of CO(2-1) emission from the 1/5 solar metallicity, Local Group dwarf galaxy NGC 6822. We achieve high ( ##IMG## [http://ej.iop.org/images/0004-637X/835/2/278/apjaa55cdieqn1.gif] $0\buildrel′′øver. 9≈ 2$ pc) spatial resolution while covering a large area: four 250 pc × 250 pc regions that encompass ##IMG## [http://ej.iop.org/images/0004-637X/835/2/278/apjaa55cdieqn2.gif] $\sim 2/3$ of NGC 6822's star formation. In these regions, we resolve ##IMG## [http://ej.iop.org/images/0004-637X/835/2/278/apjaa55cdieqn3.gif] $\sim 150$ compact CO clumps that have small radii (∼2-3 pc), narrow line width ( ##IMG## [http://ej.iop.org/images/0004-637X/835/2/278/apjaa55cdieqn4.gif] $\sim 1$ km s −1 ), and low filling factor across the galaxy. This is consistent with other recent studies of low-metallicity galaxies, but here shown with a ##IMG## [http://ej.iop.org/images/0004-637X/835/2/278/apjaa55cdieqn5.gif] $15× $ larger sample. At parsec scales, CO emission correlates with ##IMG## [http://ej.iop.org/images/0004-637X/835/2/278/apjaa55cdieqn6.gif] $8\,μ \rmm$ emission better than with ##IMG## [http://ej.iop.org/images/0004-637X/835/2/278/apjaa55cdieqn7.gif] $24\,μ \rmm$ emission and anticorrelates with H α , so that polycyclic aromatic hydrocarbon emission may be an effective tracer of molecular gas at low metallicity. The properties of the CO clumps resemble those of similar-size structures in Galactic clouds except of slightly lower surface brightness and with CO-to-H 2 ratio ∼1-2× the Galactic value. The clumps exist inside larger atomic-molecular complexes with masses typical for giant molecular clouds. Using dust to trace H 2 for the entire complex, we find the CO-to-H 2 ratio to be ##IMG## [http://ej.iop.org/images/0004-637X/835/2/278/apjaa55cdieqn8.gif] $\sim 20\mbox-25× $ the Galactic value, but with strong dependence on spatial scale and variations between complexes that may track their evolutionary state. The H 2 -to-H i ratio is low globally and only mildly above unity within the complexes. The ratio of star formation rate to H 2 is ##IMG## [http://ej.iop.org/images/0004-637X/835/2/278/apjaa55cdieqn9.gif] $\sim 3\mbox-5× $ higher in the complexes than in massive disk galaxies, but after accounting for the bias from targeting star-forming regions, we conclude that the global molecular gas depletion time may be as long as in massive disk galaxies.